PENTINGNYA PEMURIDAN BAGI PERTUMBUHAN GEREJA PADA MASA KINI MENURUT MATIUS 28:19-20 - Boyman Aspirasi Zebua; Suryaman Lugu (Misioner, 2023)
This article discusses the importance of discipleship in the church. This means that in the early church until today's church there is great emphasis on making discipleship possible, because this is the Great Commission of Jesus before ascending to heaven. The Great Commission in Matthew 28:19-20, this is an order that was delivered directly by the Lord Jesus to His disciples before He ascended into heaven and is now in the teachings of Christianity, in the church. And churches that practice discipleship are not only considered to have a narrow understanding of the Great Commission, they are also considered to be churches that truly have high morality. So this research aims to discuss the importance of discipleship for the growth of the church today according to the Book of Matthew 28:19-20. The research method used in writing this article is the literature method. The results of the study show that discipleship plays an important role, that is, discipleship is carried out to produce disciples of Christ. So, the essence of the whole process of discipleship is so that the individual can grow and become a disciple of Christ, has the values of truth and wants to walk and become a follower who is willing to be formed to make disciples for the next generation, so that the goal of discipleship to become more like Christ can be achieved.